(untitled) (Journal of Informatics and Mathematical Sciences, 2025)
Nazarov uncertainty principle is established for the Fourier transform and the continuous modulated shearlet transform on the groups of the form \(R^n × K\), where \(K\) is a locally compact group. As special cases, Nazarov uncertainty principle follows for the Gabor transform, the shearlet transform and the wavelet transform on these groups.